Il Rousseau di Antoni - Mattei, Francesco (Studi sulla Formazione/Open Journal of Education, 2013)
Carlo Antoni belongs to the crowded and well-known rank of Croce’s followers. While continuing to be grateful to Croce, he starts distancing himself from him in his Commentary to Croce (1955). He thus engages himself in the neo-Natural Law path and forges his own liberal-democratic conception of the society and of the State. Making the curtain between ethics and politics permeable, he tries to draw together, in a dialectical way, these two moments. In this light he reads Rousseau and his concept of “General Will”. The Geneva philosopher seems to him a strong link in the theoretical chain of “Ethical state”, starting from Hobbes and, through Fichte and Hegel, progressing to Gentile. Antoni’s position was not deemed noteworthy by the majority of post-gentilian disciples, but also by the large crowd of the intellectuals once faithful to Actualism and, later on, enthousiast Marxist converts.